Science Teachers' Knowledge Development - van Driel, Jan H. (Cultural and Historical Perspectives on Science Education Ser., 2021)
"In this volume, Jan van Driel presents an overview of his research on the professional knowledge that science teachers develop and enact in their teaching to promote student understanding and engagement in science. Using a selection of ten of his best publications, van Driel explains his journey from a chemistry teacher to an international leader in research in science education. He highlights collaborative projects with colleagues and students that have contributed to a better understanding of the nature of science teachers' professional knowledge and how it develops in the context of teacher education and reforms of science education. He discusses the impact of this research on the international research community, and on the practice and policy of science education"--